Search for Low Mass Vector Resonances Decaying to Quark-Antiquark Pairs in Proton-Proton Collisions at $\sqrt{s}=13\text{ }\text{ }TeV$ - CMS collaboration (2231 authors) (2017)
A search is reported for a narrow vector resonance decaying to quark-antiquark pairs in proton-proton collisions at s=13  TeV, collected with the CMS detector at the LHC. The data sample corresponds to an integrated luminosity of 2.7   fb-1. The vector resonance is produced at large transverse momenta, with its decay products merged into a single jet. The resulting signature is a peak over background in the distribution of the invariant mass of the jet. The results are interpreted in the framework of a leptophobic vector resonance and no evidence is found for such particles in the mass range of 100–300 GeV. Upper limits at 95% confidence level on the production cross section are presented in a region of mass-coupling phase space previously unexplored at the LHC. The region below 140 GeV has not been explored by any previous experiments.